The Tale of Zatoichi Continues Based on a Short Story by Kan Shimozawa - Mori, Kazuo; Honda, Shôzô; Katsu, Shintaro; Mizutani, Yaeko; Banri, Masayo (Criterion, 2019)
"The Tale of Zatoichi" proved so popular that a follow-up went into production the same year. Here, Zatoichi is hired to give a massage to a powerful political official who, he discovers, is mentally ill - a secret that the nobleman's retinue is determined to keep at any cost. This second Zatoichi film picks up the pace, featuring bigger action sequences, tighter plotting, and a mysterious one-armed swordsman played by star Shintaro Katsu's brother Tomisaburo Wakayama (Lone Wolf and Cub). [www.criterion.com]
Keywords: Blu-Ray-Disc